2022
DOI: 10.3389/fphar.2022.1071897
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of ferroptosis and the potential therapeutic targets of ferroptosis signaling pathways for glioblastoma

Abstract: Ferroptosis is a newly identified form of cell death that differs from autophagy, apoptosis and necrosis, and its molecular characteristics include iron-dependent lipid reactive oxygen species accumulation, mitochondrial morphology changes, and membrane permeability damage. These characteristics are closely related to various human diseases, especially tumors of the nervous system. Glioblastoma is the most common primary malignant tumor of the adult central nervous system, and the 5-year survival rate is only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Several investigators have shown the role of ferroptosis in the various organ-related disorders in the body [ 15 ]. Zhang and their team reported the involvement of ferroptosis in the various disorders associated with acute kidney injury, cancer, hepatic fibrosis, PDs, and ADs [ 18 ]. More especially, it is involved in all types of cancer of the liver, gastrointestinal tract, kidney, and lungs [ 185 , 186 ].…”
Section: Neurological Diseases Associated With Signaling Pathways Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have shown the role of ferroptosis in the various organ-related disorders in the body [ 15 ]. Zhang and their team reported the involvement of ferroptosis in the various disorders associated with acute kidney injury, cancer, hepatic fibrosis, PDs, and ADs [ 18 ]. More especially, it is involved in all types of cancer of the liver, gastrointestinal tract, kidney, and lungs [ 185 , 186 ].…”
Section: Neurological Diseases Associated With Signaling Pathways Of ...mentioning
confidence: 99%
“…In all these disorders, ferroptosis is involved which mediates a cascade of molecular pathways. Ferroptosis activates several molecules that encourage various pathways for GBS, AD, PD, and stroke [ 18 ]. Previous investigations have shown that Fe 2+ ions-based glutathione (GSH) activation results in the formation of ROS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of mitochondrial metabolism in cancer became a hot research topic both for basic biology and for translational studies involving drug development and response to other forms of cancer treatment (38)(39)(40)(41)(42)(43)(44)(45). In this review, we will focus on the use of advanced confocal and widefield microscopy for research on cancer metabolism in live cells.…”
Section: Introductionmentioning
confidence: 99%